Implementasi Model Pembelajaran Quantum Teaching Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar Kelas IV pada Materi Daur Hidup Hewan - Indah Kurniasari; Ridwan Jusuf; Umar M. Sadjim (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This study aims to improve student learning outcomes in animal life cycle material in class IV Elementary school through the application of quantum teaching models. The method used is Classroom Action Research (CAR) which is carried out in two cycles, each cycle consisting of: 1) Planning, 2) Action, 3) Observation, 4) Reflection, by making class IV Elementary school as research subjects. The results of the first cycle test average class achievement 54.58, there are 11 students who completed (45.83%) are in the less category, with a mastery of classical learning 70%. While the results of the second cycle test increased, with an average achievement of 90.41 in the excellent category, there were 22 students who completed (91.66%) with a classical learning completeness of 70%. So, it can be concluded that student learning outcomes from cycle I to cycle II increased by 45.83% or as many as 11 students.